AB0311 Results of screening for tuberculosis infection in patients with rheumatoid arthritis before and on treatment with biological dmards. (15th June 2017) - Karateev, D; Borisov, S; Fomina, T; Loukina, G; Luchikhina, E; Guntupova, L; Satybaldyev, A
Abstract : Background: The prevalence of tuberculosis infection in Russia is much higher than in Western Europe. Therefore, screening for TB infection in patients with RA before therapy with biological agents is of particular importance. At the same time, reliable information on the results of screening are very few. Objectives: Explore the results of the application of different methods of diagnosis of tuberculosis infection in RA patients before and during treatment with biological agents. Methods: We used the data from the Russian register "Observational REgister of arthritis in cLinical practice" (OREL). 1471 RA patients were screened for TB infection before prescribing biologics, of whom 829 patients were exposed to TB infection monitoring on therapy by biologics. The group included 21.1% men, 78.9% women; at the time of initial screening age was 50, 0±0, 4 years, the duration of the disease 8, 5±3, 8 yrs, 68, 3% RF +, 85.1% anti-CCP +, DAS28-ESR 5, 7±1, 1, 95, 7% used synthetic DMARDs, 60, 1% used systemic steroids. We used PPD (Mantoux) test, Diaskin test (intradermal test with tuberculosis recombinant allergens CFP10-ESAT6) and QuantiFERON-TB Gold (QFT) test (in some patients), chest X-ray, chest CT scan (if needed), all the patients were consulted by phthisiatrician. PPD and Diaskin test results were considered positive if the papule was ≥5 mm. Duration of treatment with biologics (anti-TNFs and others) varied widely (2–154 months), making a total of 2552, 4 patient-years. Results: At screening, we got 40, 3% positive results of PPD test (significantly more in younger patients and patients who did not receive steroids), 16, 5% positive results of Diaskin test (with no significant correlations with age and steroids). Positive results matched in 19.9% of cases, negative - in 51.9%. Discordant results in 217 patients were in 92, 2% cases related to negative results of Diaskin in PPD-positive persons. Active TB was found after additional examination in 3 (0, 2%) patients, inactive TB-related changes were revealed in 124 (8, 8%) patients. Positive PPD and Diaskin results, but not QFT, correlated with signs of inactive TB lesions. Positive results of PPD and QFT tests matched in 36.5% of cases, negative - in 18.7%, Diaskin and QFT – in 33, 6% and 41, 1% of cases resp. As a result of screening, 224 pts were treated by isoniazid or combination of anti-TB drugs before initiation of biologics. On treatment with biologics, 114 (13, 7%) pts became PPD-positive and 56 (6, 8%) Diaskin positive, active TB was diagnosed in 8 (0, 97%) pts. Conclusions: In carrying out TB screening before prescribing biologics in high-risk population of TB infection it is reasonable to use both PPD and Diaskin tests, and repeat them every 6 months on treatment. Disclosure of Interest: None declared